Design, Optimization and Evaluation of Peg-Coated Memantine Loaded PLGA Nanoscaffolds For Management of Alzheimer's Disease - Rani, Varsha (IIT(BHU) Varanasi, 2023)
Abstract is available in the content.
Keywords: Design; Optimization and Evaluation; Peg-Coated Memantine; Loaded PLGA Nanoscaffolds; Management of Alzheimer's Disease